Biomimetic fibrin–hyaluronan hydrogels for nucleus pulposus regeneration. (May 2014) - Li, Zhen; Kaplan, Keren Mevorat; Wertzel, Abraham; Peroglio, Marianna; Amit, Boaz; Alini, Mauro; Grad, Sibylle; Yayon, Avner
Aim: To develop a biomimetic polymeric injectable hydrogel that can support nucleus pulposus (NP) regeneration.Materials & methods: Natural polymer-based hydrogels were synthesized using fibrinogen (FBG) and hyaluronic acid (HA), conjugated by a novel two-step procedure. Bovine NP cells were cultured in FBG–HA conjugate-based 3D beads in vitro and in a nucleotomized organ culture model.Results: FBG–HA conjugate-based hydrogels prepared with 235 KDa HA at a FBG/HA w/w ratio of 17:1 showed superior gel stability and mechanical properties and markedly increased glycosaminoglycan synthesis compared with a FBG/HA mixture-based hydrogels or fibrin gels. Gene-expression levels of NP markers were maintained in vitro . In organ culture, NP cells seeded in FBG–HA conjugate-based hydrogels showed better integration with native NP tissue compared with fibrin gels. Moreover, FBG–HA conjugate-based hydrogels restored compressive stiffness and disc height after nucleotomy under dynamic load.Conclusion: Specific FBG–HA conjugate-based hydrogels may be suitable as injectable materials for minimally invasive, biological NP regeneration.